1995
DOI: 10.1104/pp.107.3.687
|View full text |Cite
|
Sign up to set email alerts
|

Photosystem II Excitation Pressure and Development of Resistance to Photoinhibition (I. Light-Harvesting Complex II Abundance and Zeaxanthin Content in Chlorella vulgaris)

Abstract: The basis of the increased resistance to photoinhibition upon growth at low temperature was investigated. Photosystem II (PSII) excitation pressure was estimated in vivo as 1 -qp (photochemical quenching). We established that Chlorella vulgaris exposed to ei- than cells grown at either regime at low excitation pressure. We conclude that increased resistance to photoinhibition upon growth at low temperature reflects photosynthetic adjustment to high excitation pressure, which results i n an increased capacity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
121
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(136 citation statements)
references
References 21 publications
15
121
0
Order By: Relevance
“…A similar effect has been described in Chlorella vulgaris in response to high light treatment, which increases the excitation energy pressure on PSII (Maxwell et al, 1995). This also is consistent with the dwarf phenotype of ⌬ycf9 plants grown at low temperature, which closely parallels the effect of PSII overexcitation induced by moderate illumination at low temperature in barley (Huner et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
“…A similar effect has been described in Chlorella vulgaris in response to high light treatment, which increases the excitation energy pressure on PSII (Maxwell et al, 1995). This also is consistent with the dwarf phenotype of ⌬ycf9 plants grown at low temperature, which closely parallels the effect of PSII overexcitation induced by moderate illumination at low temperature in barley (Huner et al, 1998).…”
Section: Discussionsupporting
confidence: 81%
“…Also, the study by Schneider and Erez (2006) (23) found no effect of CO 2 dosing on rates of photosynthesis and respiration, but similar to Reynaud et al The productivity responses of the CCA and corals to CO 2 dosing are likely to be a result of a series of opposing mechanisms. Initial loss of pigmentation in the corals can result in increased productivity per remnant symbiont or per chlorophyll because of subtle increases in temperature or an increased internal light field (29,30). As severe bleaching takes over, the decline in the symbiont population (or the chlorophyll pool) overrides the increased photosynthetic efficiencies, leading to a drop in areal productivity.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in the presence of reduced Q A charge recombination reactions occur that can lead to the formation of a long-lived chlorophyll triplet state and consequently to the production of 1 O 2 , which is believed to be responsible for photodamage (70,71). The redox state of Q A depends on a balance between light absorption by the antennae and the redox state of the PQ pool (15,72). This balance is compromised in the PsaF-deficient strains, leading to over-reduction of Q A , but partially restored in the suppressor strain by lowering the excitation energy input through the antennae.…”
Section: Discussionmentioning
confidence: 99%
“…In Chlamydomonas reinhardtii the absorbance crosssections of the two photosystems are nearly balanced in state I and change to 0.15 for PSII and 0.85 for PSI in state II (11). In algae long term responses may result in a reduction of the PSII antenna size (12)(13)(14)(15)(16). Alternatively, photoautotrophs could adapt by enhancing their electron-consuming sinks through a selective increase in the capacity of CO 2 assimilation or photorespiration (17).…”
mentioning
confidence: 99%